Screening for antibacterial and cytotoxic potential of marine fungi isolated from samples collected in Ly Son Island, Quang Ngai Province - Nguyen Mai Anh, Nguyen Mai Anh; Vu, Thi Thu Huyen; Cao, Duc Tuan; Doan, Thi Mai Huong; Pham, Van Cuong; Le , Thi Hong Minh (Vietnam Journal of Marine Science and Technology, 2024)
The ocean covers almost three-quarters of our planet’s surface. Marine fungi are fungi that live in marine habitats, most of them are microscopic, either microfungi or yeasts, but many marine species that inhabit the world’s oceans are not known yet. They are well recognized as a source of many novel compounds that possess valuable pharmacological properties. In the present study, we isolated and assessed the antimicrobial and cytotoxic activities of marine fungi isolated from samples collected in Ly Son Island. From 20 samples, a total of 44 marine fungi were isolated. As a result, 33/44 strains were resistant to at least 1 tested microorganisms. Among them, there were 2 isolates VM10 and VM25 showed a broad spectrum of antibacterial activity against five to six tested pathogenic ATCC strains with low MIC values. Moreover, 4/44 extracts (VM10, VM15, VM25, and VM39) showed remarkable cytotoxic effects against HepG2 human hepatoma, MCF-7 breast cancer, and A549 lung cancer cell lines with the recorded viability of tested cancer cells ranging more than 50%. The two candidate strains were subsequently identified as Aspergillus versicolor VM10, Metarhizium sp. VM25 by using 18S rRNA sequence analysis. The promising candidate isolates were analyzed in a phylogenetic tree based on MegaX software.